Pilonidal sinus treated with crystallized phenol: An eight-year experience - Dogru, O; Camci, C; Aygen, E; Girgin, M; Topuz, Ö (Lippincott Williams & Wilkins, 2004)
PURPOSE: The aim of this study was to determine the impact of crystallized phenol on the outpatient treatment of pilonidal disease. PATIENTS AND METHODS: A retrospective analysis was undertaken of patients seen in the outpatient surgery clinic of the University Hospital, Elazig, Turkey. Age, gender, body mass index, characteristics of sinuses at initial presentation, and the recovery time of 41 patients were analyzed. The relationship between recovery time and the number of sinus openings, presence of abscess, and status of the sinuses (acute vs. chronic) were noted. RESULTS: Crystallized phenol was applied a total of 107 times on 41 patients. Seventy percent of the patients had two to three applications. Mean recovery time was 42.7 ( standard deviation of 24) days with a range of 13 to 120 days. Recurrences were observed in only two patients at the fifth and eighth months following recovery. The success rate was 95.1 percent. Median follow-up was 24 (range, 6-98) months. The status of sinuses (acute vs. chronic and presence or absence of abscess) and the number of sinus opening had no effect on recovery time (P > 0.005). CONCLUSION: Crystallized phenol treatment is a simple and inexpensive method that can be readily applied on an outpatient basis, decreasing both the recurrence rate and lost work time. We suggest that this method be considered the first-line treatment of any type of pilonidal sinus.
Keywords: pilonidal disease; crystallized phenols